Imidacloprid-mediated alterations on the salivary glands of the Neotropical brown stink bug, Euschistus heros - Castellanos, Nathaly L (Ecotoxicology (London, England), 2021)
The management of the Neotropical brown stinkbug Euschistus heros (Hemiptera: Pentatomidae) in soybean fields has been heavily dependent on the application of neonicotinoid insecticides. Neonicotinoids act primarily by impairing the function of the nicotinic acetylcholine receptors of the nervous system. These compounds also target specific organs (e.g., salivary glands), which may potentiate their insecticidal efficacy. Here, we evaluated whether the exposure to the neonicotinoid imidacloprid would cause cytomorphological changes in the salivary glands of E. heros. First, we determined the lethal concentrations (LCs) of imidacloprid through contact and ingestion. Subsequently, the cytomorphology of the salivary glands were evaluated in insect groups that survived exposure to the LC5 (3.75 mg a.i./L), LC50 (112.5 mg a.i./L), or LC75 (375.0 mg a.i./L, equivalent to the recommended field rate) doses. Imidacloprid induced apoptosis and necrosis in the salivary gland cells according to the insecticide concentration and salivary gland region. All concentrations increased apoptosis and injured cells (e.g., vacuolization, chromatin condensation, swelling of organelles, and plasma membrane rupture) in the principal and accessory salivary glands. Individuals that survived exposure to the highest concentrations (i.e., LC5 and LC50) were more affected, and exhibited several necrotic cells on their main principal salivary glands. Collectively, our results indicate that imidacloprid exerts toxic effects on the non-target organs, such as the salivary glands, which increases the efficacy of this compound in the management of stink bug infestations